Servant Leadership in Improving the Performance of Village Apparatus in West Sumatra: A Systematic Literature Review - Muskinta; Yunia Wardi; Rino (International Journal of Digital Marketing Science, 2026)
In today's modern era, it is crucial to pay attention to servant leadership because many employees still don't implement it in accordance with its duties and functions, which can impact employee performance. This study aims to determine the effect of servant leadership on employee performance. This study is a systematic literature review involving 20 articles obtained from Google Scholar. The analysis of these articles explains that servant leadership has a positive and significant influence on employee performance. Therefore, servant leadership is important to consider because it can make a significant contribution to improving employee performance.